Distress in soft‐tissue sarcoma and gastrointestinal stromal tumours patients—Results of a German multicentre observational study (PROSa). Issue 10 (18th August 2022) - Eichler, Martin; Hentschel, Leopold; Singer, Susanne; Hornemann, Beate; Hohenberger, Peter; Kasper, Bernd; Andreou, Dimosthenis; Pink, Daniel; Jakob, Jens; Arndt, Karin; Kirchberg, Johanna; Richter, Stephan; et al.
Abstract: Objective: Soft tissue sarcomas (STS) and gastrointestinal stromal tumours (GIST) are a group of rare malignant tumours with a high and heterogenous disease burden. As evidence is scarce, we analysed the prevalence of increased emotional distress and identified distress‐associated factors in these patients. Methods: The PROSa‐study (Burden and medical care of sarcoma) was conducted between 2017 and 2020 in 39 study centres. Cross‐sectional data from adult STS and GIST patients were analysed. Distress was measured with the Patient Health Questionnaire (PHQ‐4). The relation of socioeconomic and clinical factors with distress was explored in adjusted logistic regression models. Results: Among 897 patients, 17% reported elevated anxiety and 19% reported depression. Unemployed patients (odds ratio [OR] 6.6; 95% CI 2.9–15.0), and those with a disability pension (OR 3.1; 95% CI 1.9–5.0) were more likely to experience distress compared to employed patients. Also, patients with a disability pass had higher odds of increased distress than those without (OR 1.8; 95% CI 1.2–2.7). Lowest distress was observed in patients 2 to <5 years and ≥5 years after diagnosis (comparison: <6 months) (OR 0.4; 95% CI 0.2–0.6) and (0.3; 95% CI 0.2–0.6). Patients with thoracic STS (vs. lower limbs) had twice the odds to experience distress (OR 2.0; 95% CI 1.1–3.6). Distress was seen almost twice as often in patients with progressive disease (vs. complete remission) (OR 1.7; 95% CI 1.1–2.8). Conclusion: The prevalence of elevated distress in STS and GIST patients is high. In unemployed patients, in those with a disability pension and in newly diagnosed patients a noticeable increase was observed. Clinicians should be aware of these factors and consider the social aspects of the disease.